Recruitment Process’ Characteristics as Presented in the European Company Survey – European Union vs Romania 2019 Data - Dana Ichim Somogyi (Ovidius University Annals: Economic Sciences Series, 2022)
This paper analyses the data provided through the European Company Survey – 2019, recruitment process’ characteristics of the EU’s companies compared to the Romanian companies. The data scrutinized provided information for the new employees recruited since 2016, how difficult it has been to find personnel with the required skills for the vacant jobs, what were the characteristics searched among the candidates, the percentage of the candidate chosen without the required skill level. When it comes to looking to find suitable candidates, over 60 % of the Romanian and European companies consider internal personnel fitted for the new position. According to the data researched, both Romanian and EU’s companies do not tend to employ a candidate without the required skill level. Therefore, investing in training and internship programs for the current employees and young people could reduce the skill mismatch and prepare the candidates for the new vacant positions.